Empathy as Political Action Can Empathic Engagement Disrupt Narratives of Conflict in Israeli-Palestinian Relations - Wilmer, Franke (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Democracy and peace rest on the ability of political institutions to channel conflict nonviolently. Most of the nearly two hundred states in the world today, however are not the product of negotiated social contracts. Rather, they came into existence as a result of political violence – imperialism, conquest, border wars, revolution, civil wars, anti-colonial independence movements, and the disintegration of empires. State formation thus often leaves a legacy of grievances and identities shaped in part by narratives and experiences of historical injury and victimization. Identity narratives are implicated not only in interstate conflict, but also in “ethnic” or “communal” conflicts within states. Can collective political action aimed at evoking empathy across the divide of identity-based enmity counter, challenge, or even disrupt these narratives of victimization and open spaces for the development or strengthening of identities committed to “what we have in common” as well as “how we are different,” and thus contribute to de-escalating, mitigating, resolving, or avoiding violent conflict altogether?